Пріоритетні напрями та принципи реалізації державної політики щодо забезпечення сталого розвитку - Куценко, В.І.; Гаращук, О.В.; Топчій, О.О. (Економіка природокористування і сталий розвиток, 2020)
Досліджено сутність сталого розвитку, визначено правові, економічні, соціальні, гуманітарні й організаційні основи та чинники його забезпечення. Наголошено на важливості державної політики у сфері сталого розвитку. Обґрунтовано ідеї, методи та перспективні напрями впровадження механізмів реалізації пріоритетних завдань сталого соціо-еколого-економічного розвитку. The article notes that during the current period of Ukraine undergoing fundamental transformations in the economy and society as a whole. In this regard, there is a need to form a new socio-economic model designed to ensure sustainable development. It also corresponds to Ukraine’s aspirations for integration into the European community. However, today the situation on the implementation of the principles of sustainable development in Ukraine is unsatisfactory, which, in particular, is expressed in the low standard of living of the population and its social protection, as well as in the inadequacy of measures taken in the field of environmental protection. This situation requires the construction of an integrated system of state policy aimed at ensuring sustainable development, which includes coordination of activities in the environmental, financial, economic and social spheres. All this should contribute to the protection of national interests, ensuring security for every citizen and society as a whole.
In this regard, it is noted that in Ukraine there are significant problems in terms of accessibility of social services, ensuring social justice, achieving economic efficiency and environmental safety. The solution to these problems should be facilitated by the current decentralization policy. Within its framework, the creation of united territorial communities is taking place, which should positively affect the provision in each of them of conditions for the implementation of the principles of sustainable development. Indeed, it is on the territory of such communities that there are prerequisites for overcoming the structural imbalances that take place in the economy and condition the irrational use of all resources, including natural ones. As a result of this, the technogenic load on the environment should decrease. The study of social security problems at the level of the united territorial communities, including monitoring of its main indicators, gives reason to assert the need to improve the management system, which should ensure the accessibility of social goods and fairness in their distribution.
Thus, ensuring sustainable development should be considered as a priority area of socio-economic development of Ukraine. This provides for such public policy measures as: the provision of unemployment benefits; ensuring a constant increase in the well-being of the population and strengthening its social protection; reduction of inflation and ensuring economic growth due to the successful solution of scientific and technical problems, including the introduction of effective forms of combining science and production; increasing environmental requirements for the economy. All this should contribute to the realization of the goal of achieving sustainable development.